Parapionosyllis (Polychaeta: Syllidae: Exogoninae) from Tenerife (Canary Islands, Spain) with description of a new species and new records - Riera, Rodrigo; Núñez, Jorge; Brito, María D.c. (Zootaxa, 2006)
Three species of Parapionosyllis: P. minuta (Pierantoni, 1903), P. macaronesiensis Brito, Núñez & San Martín, 2000 and a new species P. abriguensis, were recorded from shallow subtidal sandy substrates of Tenerife. The new species is characterized by having bidentate ventral simple chaetae and a marked dorso-ventral gradation in the length of the compound chaetae. Data on the ecology of these species, as well as a key for all Parapionosyllis known from the Canary Islands are provided.